Serum profiles of free and conjugated neuroactive pregnanolone isomers in nonpregnant women of fertile age - Havlíková, Helena; Hill, Martin; Kancheva, Lyudmila; Vrbíková, Jana; Pouzar, Vladimír; Cerny, Ivan; Kancheva, Radmila; Stárka, Luboslav (The Journal of clinical endocrinology and metabolism, 2006)
BACKGROUND: Pregnanolone isomers (PI) with a hydroxy group in the 3alpha-position are neuroinhibitors operating via positive modulation of GABA(A) receptors. The 3beta-PI and sulfates of PI and pregnenolone exert the opposite effect. In addition to the brain's in situ synthesis, some circulating steroids can penetrate the blood-brain barrier. METHODS: To assess the physiological impact of peripheral endogenous neuroactive pregnanolone isomers and their polar conjugates in women, serum allopregnanolone (P3alpha5alpha), isopregnanolone (P3beta5alpha), pregnanolone (P3alpha5beta), epipregnanolone (P3beta5beta), pregnenolone, estradiol (including their polar conjugates), and additional steroids were measured in 16 women in the follicular and luteal phases of the menstrual cycle using gas chromatography/mass spectrometry and RIA for the analysis. Linear models and Spearman's correlations were used for data evaluation. RESULTS AND DISCUSSION: The levels of conjugated PI were from one to almost three orders of magnitude higher in comparison with the free steroids. The results indicate that a substantial proportion of the progesterone is metabolized in the sequence progesterone-->5beta-dihydroprogesterone-->P3alpha5beta-->conjugated P3alpha5beta. The sulfation of PI and particularly of P3alpha5beta moderates the levels of free PI and restrains estradiol biosynthesis via progesterone degradation. PI including the conjugates reflected changing progesterone formation during the menstrual cycle. In the follicular phase, the positive correlation with conjugated pregnenolone, the independence of progesterone, and the negative age relationships of PI indicate their adrenal origin. The dependence on progesterone and the independence of conjugated pregnenolone suggest a gonadal source of PI in the luteal phase. The neuroactivating PI prevailed over neuroinhibiting PI.
Keywords: pregnenolon; Aging; Receptors, GABA-A; isomerie; Dehydroepiandrosterone; Follicular Phase; Adult; Luteal Phase; folikulární fáze; stárnutí; progesteron; ženské pohlaví; Gas Chromatography-Mass Spectrometry; Humans; pregnanolon; Estradiol; plynová chromatografie s hmotnostně spektrometrickou detekcí; Progesterone; luteální fáze; receptory GABA-A; Pregnenolone; dehydroepiandrosteron; dospělí; Female; Isomerism; Pregnanolone; estradiol; lidé